Analisis Perlakuan Selisih Kurs Mata Uang Asing Pada PT Elang Mahkota Teknologi Tbk (Jurnal Manajemen Kreatif dan Inovasi, 2024)
The aim of this research is to analyze the treatment of foreign exchange differences at PT. Elang Mahkota Teknologi Tbk (EMTK), focusing on transaction management, the use of functional currency, and exchange rate risk mitigation. The research method employed is qualitative, with PT EMTK as the research subject. Data was obtained through literature review, referring to the Annual Reports of PT EMTK. The study indicates that PT EMTK adopts a cautious approach in handling foreign exchange transactions. The majority of business units use the Indonesian Rupiah as the functional currency, and the monetary assets and liabilities are adjusted to the exchange rates at the reporting date. Despite the absence of an official hedging policy, the company still considers current market conditions, especially regarding cash and cash equivalents balances in USD. Additionally, the research reveals that PT EMTK conducts sensitivity analysis on exchange rate risk, measuring the impact of exchange rate fluctuations on pre-tax profits. Overall, the company diligently monitors foreign exchange rate risks and takes proactive measures against external factors that may affect financial performance.